Predictors of Outcome in Juvenile Myoclonic Epilepsy - Chen Y; Chen J; Chen X; Wang R; Zeng J; Wang F; Miao J (Dove Medical Press, 2020)
Yiqian Chen,1,* Jingzhen Chen,1,* Xingyu Chen,1,* Ru Wang,2 Jianqi Zeng,1 Feng Wang,3 Jiayin Miao1 1Department of Neurology, Zhongshan Hospital, Xiamen University, Xiamen 361004, People’s Republic of China; 2Department of Neurology, Weinan Central Hospital, Weinan 714000, People’s Republic of China; 3School of Computer Engineering, Jimei University, Xiamen 361021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiayin MiaoDepartment of Neurology, Zhongshan Hospital, Xiamen University, Xiamen 361004, People’s Republic of ChinaTel +86-15880281527Fax +86 592-2212328Email miaojiayin2006@163.comBackground: Juvenile myoclonic epilepsy (JME) is the most common idiopathic generalized epilepsy syndrome, accounting for 10% of all epilepsy. However, there is limited information regarding the predictors of seizure outcome. The aim of this study was to determine the predictors of seizure outcome in JME patients.Methods: A population-based retrospective study of JME patients who were treated at the Department of Neurology of affiliated Zhongshan Hospital, Xiamen University from 2008 to 2013.Results: Sixty-three patients (30 women and 33 men) were enrolled in this study. The median age at seizure onset was 14 years old, and the average duration of epilepsy was 5 years. The onset of JME at age < 16 years was found in 63.5% of patients. The epileptiform runs ≥ 3 s were observed in 35.8% patients. Febrile seizure was noted in 28.9% of patients. Among 63 patients, 40 patients (63.5%) had remission. Multivariate analysis identified the following factors as significant predictors of seizure outcome: the onset of JME at age < 16 years, epileptiform runs ≥ 3 s runs, and febrile seizure.Conclusion: The onset of JME at age < 16 years, febrile seizures and epileptiform runs ≥ 3 s might be associated with poor long-term seizure outcome in patients with JME.Keywords: juvenile myoclonic epilepsy, seizure, predictor, outcome